Composition of raft-like cell membrane microdomains resistant to styrene-maleic acid copolymer (SMA) solubilization - Harant, Karel; Čajka, Tomáš; Angelisová, Pavla; Pokorná, Jana; Hořejší, Václav (Biophysical chemistry, 2023)
An advantageous alternative to the use of detergents in biochemical studies on membrane proteins are the recently developed styrene-maleic acid (SMA) amphipathic copolymers. In our recent study [1] we demonstrated that using this approach, most T cell membrane proteins were fully solubilized (presumably in small nanodiscs), while two types of raft proteins, GPI-anchored proteins and Src family kinases, were mostly present in much larger (>250 nm) membrane fragments markedly enriched in typical raft lipids, cholesterol and lipids containing saturated fatty acid residues. In the present study we demonstrate that disintegration of membranes of several other cell types by means of SMA copolymer follows a similar pattern and we provide a detailed proteomic and lipidomic characterization of these SMA-resistant membrane fragments (SRMs).
Keywords: membránové mikrodomény; polystyreny; buněčná membrána; Membrane Proteins; membránové proteiny; Jurkat cell line; SMA copolymer; mastné kyseliny; Maleates; Cell Membrane; Polystyrenes; maleáty; Membrane Microdomains; Membrane rafts; Proteomics; proteomika; Lipidomics; Fatty Acids